Modelling inflation in China - a regional perspective - Aaron N. Mehrotra; Tuomas A. Peltonen; Alvaro Santos Rivera (European Central Bank (ECB), 2007)
We model provincial inflation in China during the reform period. In particular, we are interested in the ability of the hybrid New Keynesian Phillips Curve (NKPC) to capture the inflation process at the provincial level. The study highlights differences in inflation formation and shows that the NKPC provides a reasonable description of the inflation process only for the coastal provinces. A probit analysis suggests that the forwardlooking inflation component and the output gap are important inflation drivers in provinces that have advanced most in marketisation of the economy and have most likely experienced excess demand pressures. These results have implications for the relative effectiveness of monetary policy across the Chinese provinces.
Keywords: E31; C22; 330; China; GMM; inflation; New Keynesian Phillips curve; Regional; Inflation; Räumliche Verteilung; New-Keynesian Phillips Curve; Momentenmethode; China